Utilization of Measurement Technology in Analyzing Tidal Flooding Run Up Along Semidang Alas Maras Coast - Supiyati; Suwarsono; Harlianto, Budi; Baringin, Rolando (Formosa Journal of Computer and Information Science, 2025)
Tidal floods in the Semidang Alas Maras coast often occur and disrupt community activities. The height and area affected by tidal flood run-up is not the same every time. This research are to identify the factors that influence tidal floods and determine the effect of seasonal changes on tidal flooding run-up along Semidang Alas Maras coast by utilising measurement technology using drones. The method in this research is direct measurements of tides, visual photos topographic using drones, and also secondary data including tidal data from TMD model, rainfall, and wind data during tidal flooding. Based on the results of the study, it was found that tidal flooding run-up along Semidang Alas Maras coast was influenced by tides, high rainfall and wind. The mixed tide type of Semidang Alas Maras is Mixed Tide Prevailing Semidiurnal with a Formzhal number of 0.76. The area affected by the tidal flood run-up for the criteria of no danger and less danger every season is the same. Meanwhile, the criteria for moderately dangerous, dangerous and very dangerous vary every season. The highest area value occurring in the western season, the criteria for moderately dangerous 20% with an area of 83.06 Ha, 21% hazard with an area of 85.78 Ha, and very dangerous 23% with area of 93.95 Ha